Recognizing the state's "duty to regulate": The mindset needs to shift - Andrea Shemberg (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
As global discussions on IIA reform continue, this Perspective offers one idea on how to help facilitate reform through the shifting of mindsets of arbitrators, States and companies. Recent progress in business and human rights offers valuable lessons for how the power of ideas can contribute to meaningful change.
Keywords: 330